(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
Innovative pedagogical approaches play a crucial role in enhancing the quality of education by integrating modern methodologies with traditional teaching techniques. Despite the growing interest in pedagogical innovations, there remains a knowledge gap regarding their direct impact on student engagement, learning outcomes, and long-term academic success. This study employs a mixed-method approach, combining qualitative surveys and experimental analysis to evaluate the effectiveness of innovative teaching strategies in diverse learning environments. The findings indicate that technology-enhanced and student-centered learning models significantly improve knowledge retention, problem-solving skills, and overall academic performance compared to conventional methods. The results further highlight the necessity of continuous teacher training and institutional support to effectively implement these innovations. These insights have important implications for educators, policymakers, and curriculum developers in fostering an adaptive and inclusive education system that meets the evolving demands of the 21st century.